Los Angeles modernism revisited : houses by Neutra, Schindler, Ain, and contemporaries : Gregory Ain, Craig Ellwood, Leland Evison, A. Quincy Jones, Ray Kappe, John Lautner, Allyn Morris, Richard Neutra, Rudolph Schindler - Nierhaus, Andreas (Park Books, 2019)
Two Austrian-born designers have left their indelible mark on California's residential architecture of the 1930s to 1960s. Richard Neutra (1892-1970) and Rudolph M. Schindler (1887-1953) combined modern form and inventive construction with new materials to create a truly modern vision of living that remains inspirational to the present day. This new book features twenty famous and lesser known houses from that period, designed by the two pioneers and other architects that were influenced by Neutra's and Schindler's ideas. All are marked by highly economical use and outstanding quality of space, a minimalist aesthetic, and by their ideal adaption to climatic conditions. They are monuments of a period as well as timeless models for contemporary and future architecture. The images by photographer David Schreyer show the buildings in their present state as a commodity of highest quality that can be, and should be, altered to meet today's changed demands to a living space. Andreas Nierhaus's texts, based on interviews, explore the relationship of the present inhabitants to their homes and what they mean to them. Together, the authors offer uniquely intimate insights into a sophisticated way of life still too little known outside California.